2021
DOI: 10.1111/nmo.14231
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood constipation and exposure to stressful life events: a systematic review

Abstract: Background Several cross‐sectional studies have reported an association between childhood constipation and exposure to stressful events. We planned to systematically review the literature on constipation and its associated stressful events. Methods PubMed, Embase, and PsycINFO databases were searched (until February 2021) using standard search terms related to “constipation” and “stress” from 0 to 18 years that describe the association between psychological stressors and constipation. Studies were screened usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…It defined child maltreatment, divorce/separation of parents, severe illness in the family, and parental job loss as home stressors. In the same way, bullying, change in school, separation from the best friend, and failure on examination as school-related stressors were associated with childhood constipation [44].…”
Section: On the Way To Quality Of Life: Stressful Life Eventsmentioning
confidence: 82%
“…It defined child maltreatment, divorce/separation of parents, severe illness in the family, and parental job loss as home stressors. In the same way, bullying, change in school, separation from the best friend, and failure on examination as school-related stressors were associated with childhood constipation [44].…”
Section: On the Way To Quality Of Life: Stressful Life Eventsmentioning
confidence: 82%
“…In agreement with our findings relating to barriers and facilitators to implementation, the importance of the context in which the child is living was highlighted by a recent SR which identified 15 primary studies which explored the 'association between childhood constipation and exposure to stressful events'. 392 The authors conclude that stressful events experienced by children (e.g. parental separation, family illness, being bullied) are associated with CFC.…”
Section: Comparison Of Findings With Guidelines and Other Systematic ...mentioning
confidence: 92%
“…This is supported by a recent SR, which concludes that lack of knowledge and understanding is a key issue faced by families/carers of children with CFC, and research to identify effective educational/ informational strategies a priority. 392 Our focus was on management of CFC in children, and -while we considered psychosocial and behavioural interventions -we did not consider the psychosocial and behavioural factors which may contribute to poor outcomes. For example, there is evidence that some children may actively avoid using school toilets 395 and concern has been raised about the impact of this on children with bowel problems.…”
Section: Focus On Treatments For Chronic Functional Constipationmentioning
confidence: 99%
“…A link was identified between psychological anxiety and pelvic floor tension. Blood flow from the rectal mucosa to the intestine and the extrinsic nerve increases [ 2 , 23 ]. Functional magnetic resonance imaging (MRI) studies have demonstrated a linked between functional gastrointestinal disorders with activation of the anterior midcingulate and posterior cingulate, as well as deactivation of the anterior cingulate cortical supragenual region, which linked to downregulation of pain signals in children who have been exposed to abuse [ 24 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%